Securing Data Using Deep Hiding Selected The Least Significant Bit And Adaptive Swarm Algorithm - Bashar Izzeddin Issa Aljidi; Sundresan A/L Perumal; Sakinah Ali Pitchay (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Indexed by Scopus